Legal Aspects of Involvement of the Indonesian National Army in Countering Terrorism in Indonesia - Beny Abukhaer Tatara; Anastasya Sukma Kundhalini; Bisma Abdurachman; Pujo Widodo (Criminal of Law Department, Faculty of Law, Pattimura University, 2022)
Terrorism is a crime that is included in the category of extraordinary crimes. So, to overcome it, it is necessary to carry out extraordinary measures, one of which is by involving military forces in this case the Indonesian National Army (TNI). The purpose of writing this article is to analyze the legal aspects of the involvement of the Indonesian National Army in countering terrorism in Indonesia. The research method used is qualitative with data collection techniques in the form of literature studies. The results of the study show that the involvement of the Indonesian National Army in counter-terrorism efforts is regulated in Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2002 concerning Eradication of Criminal Acts of Terrorism into Law, Law Number 34 of 2004 concerning the Indonesian National Army and Presidential Regulation Number 62 of 2016 concerning Amendments to Presidential Regulation Number 10 of 2010 concerning the Organizational Structure of the Indonesian National Army. Currently, the draft Presidential Regulation which is the mandate of the Amendment to the Law on Criminal Acts of Terrorism to serve as a guide for the involvement of the TNI in the task of assisting the handling of terrorism has been discussed and approved by the House of Representatives (DPR RI), it is just waiting for the President signature to be ratified.